Effect of Telehealth Implementation on the Quality of Nursing Care in Chronic Disease Patients - Rahayu Tri Nuritasari (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
Chronic diseases require continuous nursing care; however, barriers such as limited access to services, low frequency of control, and suboptimal communication between nurses and patients especially in outpatient settings are still common. Telehealth has emerged as an alternative service, yet its effect on the quality of nursing care requires further scientific investigation. This study aimed to analyze the effect of telehealth implementation on the quality of nursing care in patients with chronic diseases. A quantitative study with a cross-sectional design was conducted at Semen Padang Hospital involving 120 patients selected through purposive sampling. Data were collected using questionnaires measuring nursing care quality, including assessment, planning, implementation, evaluation, and therapeutic communication. Telehealth variables included technology use, service accessibility, and digital interaction between healthcare providers and patients. Data were analyzed using simple linear regression with a significance level of 0.05. The results showed that 68.3% of respondents rated telehealth implementation as good, while 72.5% rated nursing care quality as good. Regression analysis revealed a significant positive effect (p=0.001; β=0.462), with an R² value of 0.213, indicating that telehealth contributed 21.3% to nursing care quality improvement. In conclusion, telehealth significantly improves nursing care quality and can support sustainable healthcare service development.